2018
DOI: 10.1002/slct.201702818
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Catalytic Systems Formed by Palladium and Acyl‐Substituted Imidazolium Salts

Abstract: Amino amides, which are readily accessible from amino acids, were used in the preparation of both monoamido and diamido functionalized imidazolium salts in very straightforward protocols. Different catalytic systems formed with palladium(II) acetate and acyl functionalized imidazolium salts were tested in the Matsuda‐Heck reaction. The comparative study revealed that the presence of one carbamoyl moiety in the N‐heterocyclic carbene precursor is more beneficial during the catalytic process. Thus, better activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…The IL 1‐ n ‐butyl‐3‐methylimidazolium chloride ( C 4 MImCl ), 95%, was used as purchased from Sigma‐Aldrich (St. Louis, Missouri). A literature procedure was used for the synthesis of 1‐carboxymethyl‐3‐methylimidazolium chloride ( HO 2 CC 1 MImCl ), and the spectral data were in accordance with those reported …”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…The IL 1‐ n ‐butyl‐3‐methylimidazolium chloride ( C 4 MImCl ), 95%, was used as purchased from Sigma‐Aldrich (St. Louis, Missouri). A literature procedure was used for the synthesis of 1‐carboxymethyl‐3‐methylimidazolium chloride ( HO 2 CC 1 MImCl ), and the spectral data were in accordance with those reported …”
Section: Methodsmentioning
confidence: 96%
“…A literature procedure was used for the synthesis of 1-carboxymethyl-3-methylimidazolium chloride (HO 2 CC 1 MImCl), and the spectral data were in accordance with those reported. 17 The commercial AP was treated with ethanolic IL solutions, containing IL amounts corresponding to 1.0 wt% of the AP mass. The AP, immersed in the IL solution, was placed in an ultrasonic bath at 50 C for 1 h. Then, the AP with adsorbed/absorbed IL was dried in an oven at 110 C for 12 h. The HNBR masterbatches with untreated or IL-treated AP were prepared as follows: HNBR (20.0 g) was added to 290 mL of THF, and the mixture was left under magnetic stirring, at room temperature, until complete dissolution of the rubber.…”
Section: Introductionmentioning
confidence: 99%
“…From these compounds, it is possible to design a variety of catalytic systems. We employed functionalized imidazolium derivatives as precursors for N-heterocyclic carbene (NHC) ligands for palladium in organic transformations. , In combination with metal salts, such as iron­(III) chloride, imidazolium salts can produce iron-based Lewis acid ionic liquids (IBLAILs), which proved to be very versatile catalytic systems . Furthermore, we employed metal–organic frameworks based on imidazolium–dicarboxylate as efficient and robust catalysts for organic transformations. , Recently, we have envisioned the use of imidazole derivatives bearing carboxylic acids as catalytic systems by themselves.…”
Section: Introductionmentioning
confidence: 99%
“…In Hg drop experiments of three types of C‐C coupling reactions, when a drop of mercury was added to the reaction mixture before starting the model reactions, the suppressions of three types of coupling reactions have been observed, which indicated that these reactions are heterogeneous and further proved that Pd(0) is the active catalytic species. Therefore, the way in these cross‐coupling reactions should be that imidazolium salt as molecular ligand formed Pd‐NHC bond …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the way in these cross-coupling reactions should be that imidazolium salt as molecular ligand formed Pd-NHC bond. [11,51] 3 | EXPERIMENTAL [52] and 9,10-bis(chloromethyl)anthracene [32] were prepared according to the literature methods. All the reagents for synthesis and analyses were of analytical grade and used without further purification.…”
Section: Kinetic Studies Of Suzuki-miyaura Heck-mizoroki and Sonogmentioning
confidence: 99%